Management of C2 odontoid peg fragility fractures – A UK survey of spinal surgeons. Issue 3 (March 2022) - Watts, Anna; Athanassacopoulos, Michael; Breakwell, Lee; Chiverton, Neil; Cole, Ashley; Ivanov, Marcel; Tomlinson, James
Highlights: Fragility Fractures of the odontoid peg are increasing in incidence and have mortality rates higher than fragility fractures of the hip. There is wide variation in the initial treatment modality, imaging and follow-up of these injuries. Further large-scale studies are urgently required to inform best practice and standardise management in this high risk group. Abstract: Purpose: Patients sustaining fragility fractures of the C2 odontoid peg have 30-day mortality rates as high as 10% rising up to 34.1% at 1 year. Substantial controversy exists regarding optimal management of these fractures and there is a lack of national guidance to inform best practice. The aim of this study was to determine current practice in the management of these fractures throughout the United Kingdom. Methods: A UK wide, cross sectional survey was conducted, asking 10 questions regarding the initial management, imaging and follow-up of an elderly patient with a type 2 fragility odontoid peg fracture. This was publicised through the British Orthopaedic Association website and sent to all members of the Society of British Neurological Surgeons (SBNS) via email. Results: 107 Responses were received. 56% from orthopaedic consultants, 29% from neurosurgical consultants and 15% from senior spine fellows. 86% (92) of respondents choose treatment with a cervical orthosis, with 84% (77) of these opting for a semi rigid Aspen or Philadelphia collar compared to 16% (15) opting for a soft cervical collar. Three (3%) opted for operative intervention with a further three (3%) choosing Halo fixation. Nine respondents (8%) opted for no orthosis and treatment with analgesia alone. Length of immobilisation in cervical orthosis ranged from 6 to 12 weeks. Initial follow-up ranged from 1 week to 6 weeks, with 6% (6) discharged without follow up. There was also marked variation in the use of follow-up imaging with 17% (18) using plain radiographs, 62% (66) requesting lateral flexion / extension radiographs, 10% (11) using CT and 11% (12) not performing any imaging at final follow up. In 60% (64) of cases respondents did not change subsequent management as a result of imaging. Conclusion: Type-2 fragility peg fractures have high morbidity and mortality. There is marked variation in the treatment modalities used, follow-up regime and use of imaging throughout the UK. Given the rapidly increasing incidence of these injuries and the associated mortality this should be a high priority field for further research. Further large scale studies are urgently required to inform best practice and standardise management of these injuries.